Efl teenagers’ social identity representation in a virtual learning community on facebook (2012)
In this article I report the findings of a descriptive and interpretative qualitative study carried out in a public school in Bogotá, Colombia. The study aimed at analyzing, describing and exploring teenage students’ social identity representation as observed in their participation in a learning community on Facebook. Data were collected from eight active participants through artifacts and semi-structuredinterviews in the Dragster Virtual Community on Facebook. Data analysis illustrated that teenagers’ ways of expressing themselves are manifested in conversations and posts and these interactions portray and reflect their social identity inside the group. Their social representations are evaluated, accepted, or denied by the other members in the asynchronous group.En este artículo reportamos los resultados de un estudio cualitativo, descriptivo e interpretativo llevado a cabo en una escuela pública en Bogotá, Colombia. El objetivo fue analizar, describir y explorar la representación de la identidad social de los estudiantes adolescentes de inglés comolengua extranjera, observando su participación en una comunidad de aprendizaje en Facebook. Los datos de ocho participantes activos fueron recolectados a través de artefactos y entrevistas semiestructuradas en la comunidad virtual Dragster, en Facebook. El análisis de los datos muestra que las expresiones que los adolescentes usan en las conversaciones y en los diferentes tipos de publicacionesreflejan su identidad social dentro del grupo. Sus representaciones sociales son evaluadas, aceptadas o rechazadas por los demás miembros del grupo asincrónico.